Measuring up (or down?) - How the best of intention leads to undesirable consequences - Anon (Universiti Malaysia Perlis (UniMAP), 2012)
The Professorial Lecture Series by Prof. Dr. Zuraidah Mohd Zain on Measuring up (or down?) - How the best of intention leads to undesirable consequences organized by Universiti Malaysia Perlis, 31st May 2012 at Dewan Kapitol, Kangar, Perlis, Malaysia.